GE_GERICHTE P/25461/2019 vom 16. Juli 2021 - GE Cour de justice (2021)
BRIGANDAGE;COAUTEUR(DROIT PÉNAL);COMPLICITÉ;RÉVOCATION DU SURSIS;DÉTENTION AUX FINS D'EXPULSION;FIXATION DE LA PEINE | CP.140.al1.ch1; CP.25; CP.47; CP.46; LArm.33.al1.leta; CP.66.al1.letc.para